Motivasi, Pengetahuan Investasi, Self Efficacy dan Minat Investasi selama Pandemi Covid-19 - Irmayani, Ni Wayan Dian; Rusadi, Ni Wayan Purnami; Premayanti, Ketut Priya; Pradana, Putu Aditya (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p20, 2022)
This study aims to provide empirical evidence that motivation, investment knowledge, and self-efficacy affect investment interest. The data used in this study are primary data obtained by distributing survey questionnaires to the younger generation in Bali Province who have attended courses, seminars, capital market courses and have stock accounts. The sample was determined through purposive sampling technique. Data analysis technology uses Statistical Product and Service Solutions (SPSS). The results showed that motivation, investment knowledge, self-efficacy had a positive effect on investment interest. So, the research results theoretically confirm the Theory of Planned Behavior (TPB). Keywords: Motivation; Investment Knowledge; Self Efficacy; Investment Interest.